Peran Kepemimpinan Dalam Pengembangan Kompetensi Pegawai Negeri Sipil Pada Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Bali - Gede Wirata; Ni Luh Widiantini; Sri Sulandari (Journal of Contemporary Public Administration, 2021)
Leadership related to developing employees’ competencies is an important part of organization life. However, this has not been carried out properly to ensure all duties and obligations are carried out within the organization, one of which is developing the competence of organizational members. Objectives of this research are to determine the role of leadership in developing the competence of Civil Servants at BPSDM Bali; and to determine the constraints of developing the competence of Civil Servants at BPSDM Bali. This research uses qualitative descriptive method with transformational leadership theory. There were 8 (eight) informants determined using purposive sampling technique. Data collection use interview guidelines, observation and documentation. The methods and data analysis techniques were carried out by reducing, presenting data and drawing conclusions. The final stage of the analysis carried out the presentation of the results of the data presented with narrative text. From the analysis, the results show that the role of leadership in developing the competence of civil servants at BPSDM has not been maximal in mobilizing, directing and evaluating subordinates to fulfill the rights and opportunities for competency development of civil servants for 20 hours of lessons / year according to government regulation Number 11 of 2017 concerning Employee Management Civil Affairs. Furthermore several constraints are found, namely the egoism of subordinates, no leadership commitment, no strategy in accelerating employee competency development, the need for employee competency development get maximum budget support.